Red outposts in a hostile landscape: People's houses, People's parks and the reconstruction of rural southern Sweden's political geography, 1889–1909. (November 2022) - Pries, Johan; Jönsson, Erik; Mitchell, Don
Abstract: Organizing rural workers has always proved to be a challenge for the labour movement. This was especially the case in Scandinavia where well into the industrial era, labour and property relations in the agricultural countryside remained essentially feudal in character. Nonetheless, and especially in the rich agricultural districts of the southernmost province of Skåne, the Swedish labour movement had succeeded spectacularly by the interwar years. Perhaps unintuitively, a key to its success was that it focused as much money and energy on constructing new spaces of culture and leisure – so-called People's Houses and People's Parks – as it did to direct workplace organizing. Drawing on Kevin Cox's concepts of "spaces of dependence" and "spaces of engagement, " this paper explains how and why Sweden's labour unions succeeded in remaking Skåne's political geography and transformed the region into one of the strongest social-democratic districts in early-twentieth century Sweden.